THE ACADEMIC JOURNEY OF ENTREPRENEURSHIP STUDENTS IN HIGHER EDUCATION INSTITUTIONS. THE SYSTEMS THEORY APPROACH - Lucky Sibanda; Chux Gervase Iwu (National Academy of Educational Sciences of Ukraine, 2021)
In its fifth report, South Africa's Department of Higher Education and Training (DHET), published on 31 March 2020, called for institutions to carefully investigate undergraduate business education (curricula) after the business, economics, and management studies (in the Classification of Educational Subject Matter (CESM)) category presented the highest dropouts and lowest throughput rates. To understand the academic journey of entrepreneurship students, this study reviewed the literature through the lens of the General Systems Theory (GST), together with Tuckman's (1999) Tripartite Model of Motivation for Achievement (TMMA). Accordingly, this study viewed the journey of students as a dynamic system with the students having some characteristics and motivations (inputs) when entering higher education, and what the higher education institutions should do (processes) to achieve improved academic performance (output) of students. From the literature reviewed, this study suggests the need to profile students based on their pre-enrolment information and capturing the perceptions of what they think influenced their academic performance in high school. Apart from this, the need to understand the entrepreneurial profile of students has been suggested considering the importance of entrepreneurship in employment creation, especially in South Africa, with an unemployment rate of 32.6%. Thus, it is necessary to produce graduates with the much-needed entrepreneurial capabilities in the South African economy.